Load Balancing Menggunakan Algoritma Round Robin Dengan Stickness Pada AWS - Meidiana Shafira; Hidra Amnur; Rita Afyenni (SOTVI - Society of Visual Informatics, 2021)
The development of information and communication technology is increasingly sophisticated, especially in the field of networks. This development is closely related to the internet which is one of the most popular information providers today. The increasing need for information will demand fast access to get the latest information, one of which is the most dominant influencing the speed of access to a particular website is the service provider. Therefore it takes a server that has good quality and performance or has many servers so that it is not burdened on one server. Application load balancing is one of the right solutions to overcome this problem. The load balancing application will share the network load and avoid overloading one of the servers. The load balancing application method used is round robin with stickiness. When one server crashes, the load balancing application will automatically redirect requests to another server that is still functioning, so that the website can be accessed..